Fishing in life and death: Pleistocene fish-hooks from a burial context on Alor Island, Indonesia. (6th December 2017) - O'Connor, Sue; Mahirta,; Samper Carro, Sofía C.; Hawkins, Stuart; Kealy, Shimona; Louys, Julien; Wood, Rachel
Abstract: Abstract : Fish-hooks discovered among grave goods associated with an adult female burial at the Tron Bon Lei rockshelter on the island of Alor in Indonesia are the first of their kind from a Pleistocene mortuary context in Southeast Asia. Many of the hooks are of a circular rotating design. Parallels found in various other prehistoric contexts around the globe indicate widespread cultural convergence. The association of the fish-hooks with a human burial, combined with the lack of alternative protein sources on the island, suggest that fishing was an important part of the cosmology of this community. The Tron Bon Lei burial represents the earliest-known example of a culture for whom fishing was clearly an important activity among both the living and the dead.